The Blended Revolution Unveiling The Future - Fajriati Astuti; Riviyanti; Azwar Abbas (Mutiara Intelektual Indonesia Press, 2024)
In the globalized era, proficiency in English is crucial for vocational school graduates to succeed in the workforce. Despite this necessity, many vocational students struggle with inadequate English skills due to limited access to quality materials, lack of motivation, and unengaging learning methods. This study aims to explore how digital technology can enhance English language learning among vocational students, making it more effective, interesting, and accessible. A qualitative research approach was employed, involving observations, focus groups, and semi-structured interviews with English teachers. The data was analyzed thematically to identify key trends and insights. The integration of digital technology, such as language learning apps (Duolingo, Babbel) and e-learning platforms (Google Classroom, Moodle), significantly improves English language skills among vocational students. Key benefits include increased access to learning materials, more engaging and interactive learning experiences, and enhanced motivation. Furthermore, digital tools facilitate personalized learning and provide immediate feedback, which helps students improve their language skills more efficiently. The study identified several challenges, including limited access to digital devices and the internet, and varying levels of technological proficiency among students and teachers. These challenges necessitate improved infrastructure and additional training to maximize the benefits of digital technology in education. Digital technology plays a pivotal role in transforming English language learning in vocational schools. Despite challenges, its benefits in improving language skills, increasing student engagement, and preparing students for the global workforce are substantial. Schools should continue investing in digital resources and training to ensure all students can leverage these tools effectively